История хорового искусства в Китае - Бань, Цзинюй (БНТУ, 2024)
The article covers the issues of formation and development of choral art in China. Choral music performed various historical missions in different periods of the state's existence, promoted various themes of modernity and emphasized patriotism and collectivism.